7Be content in rainfall and soil deposition in South American coastal ecosystems - Pereira Cardoso, Renan (2011)
Beryllium-7 (7Be) is a cosmogenic radionuclide that enters from the atmosphere, mainly by wet deposition, being widely used to explore environmental processes. With the aim of using beryllium as an environmental tracer, we are evaluating the 7Be input through rainfalls, its soil deposition and vertical distribution in soil profile. In Niteroi City (Rio de Janeiro State, Brazil) the 7Be content in rainfall and soil were evaluated. The 7Be content in samples was determined by measuring its γ-emission at 477.6 Kev, using a special 55% efficiency high-purity germanium detector produced by Canberra. 7Be activity concentration in rainfall ranged from 0.12 ± 0.15 Bq l-1 to 1.96 ± 0.23 Bq l-1 (Mean=0.58 Bq l-1, SD=0.48 Bq l-1). The magnitude of precipitation ranged from 2.8 to 40 mm. The 7Be activity concentrations in Niteroi rains are lower than values reported from another sites. Differences in 7Be content should be expected to occur in different environment, due to the effect that latitude and altitude can have on 7Be atmospheric concentrations. 7Be wet deposition ranged from 0.39 ± 0.49 Bq m-2 to 34.8 ± 4.9 Bq m-2. The content and distribution of 7Be in soil were analyzed for the months of February and April. 7Be are presents at the first 2 cm depth and the activity concentration decrease exponentially, when depth increases. The total 7Be content in soil were 190 Bq m-2 and 330 Bq m-2 for February and April, respectively. These results are expected because 7Be are strongly retained in the first centimetres of soil and between February and April several rains have occurred, providing 7Be to soil.